Distinct strategies of diguanylate cyclase domain proteins on inhibition of virulence and interbacterial competition by agrobacteria - Xuan Lai; Manda Yu; Chiu-Ping Cheng; Erh-Min Lai (mBio)
ABSTRACT Diguanylate cyclases (DGCs) synthesize bis-(3′,5′)-cyclic diguanylic acid (c-di-GMP), a critical bacterial second messenger that coordinates diverse biological processes. Agrobacterium tumefaciens, a plant pathogen causing crown gall disease, relies on type IV secretion system for pathogenesis and type VI secretion system (T6SS) for interbacterial competition. Our study identified two putative DGCs, named diguanylate cyclase domain proteins regulating virulences A and B (DcvA and DcvB), that negatively regulate virulence through distinct mechanisms. DcvA suppresses virulence by targeting the VirA/VirG two-component system downstream of VirA. This inhibition is independent of c-di-GMP levels. DcvB positively regulates biofilm formation, inhibits T6SS-mediated interbacterial competition, and suppresses virulence via the ChvG/ChvI two-component system downstream of ChvG. These effects are dependent on its cyclase activity and the associated increase in intracellular c-di-GMP levels. These findings suggest that DcvA and DcvB control virulence and interbacterial competition using different mechanisms in Agrobacterium. DcvA suppresses virulence, independent of c-di-GMP, and DcvB enhances global c-di-GMP concentration to promote biofilm formation and inhibits virulence and T6SS antibacterial activity. The findings provide understanding of how DGC domain proteins orchestrate complex regulatory networks to balance virulence, biofilm formation, and interbacterial competition, enabling them to adapt to changing environments.IMPORTANCEBacteria produce second messengers, such as c-di-GMP, to regulate various cellular processes, including biofilm formation, virulence, and bacterial antagonism. Diguanylate cyclases (DGCs) catalyze the biosynthesis of c-di-GMP and function to cope with changing environments through targeting specific effector proteins. In this study, we uncover that phytopathogenic agrobacteria deploy two DGC domain proteins to suppress virulence and interbacterial competition through two different regulatory pathways. One exhibits the DGC activity, enhancing global c-di-GMP concentration to elevate biofilm formation and inhibit virulence and antibacterial activity, while the other specifically suppresses virulence, independent of c-di-GMP biosynthesis. Our findings provide new insight into the distinct regulatory mechanisms of DGC domain proteins on regulating virulence and interbacterial competition, highlighting potential new strategies for controlling Agrobacterium pathogenicity.